Arquitectura foliar de diez especies de encino (quercus, fagaceae) de México - Rodríguez Rivera, Isaac Said; Romero Rangel, Silvia (Instituto de Ecología, A.C., 2007)
The study of the leaf architecture of ten species of the genus Quercus was made. Four types of venation were observed: the mixed craspedodromous-camptodromous in Q. deserticola, Q. eduardi, Q. frutex and Q. greggii; mixed craspedodromous-eucamptodromous in the species Q. obtusata, Q. potosina and Q. scytophylla; brochidodromous in Q. elliptica, and camptodromous in Q. repanda and Q. splendens. All the taxa have five orders of venation; nine species show quadrangular areoles and only Q. repanda shows pentagonal areoles. The species of the section Quercus have anomocitic stomates, while those of the section Lobatae have cyclocitic stomates. Stomates are present only on abaxial surface of the leaf. The stomatal indices obtained ranged from 36 to 88 in the section Quercus and from 19 to 42 in the section Lobatae.